Immune responses potentially involved in the gestational complications of Brucella infection - Zavattieri, Lucia (2023)
Infection by Brucella species in pregnant animals and humans is associated with an increased risk of abortion, preterm birth, and transmission of the infection to the offspring. The pathogen has a marked tropism for the placenta and the pregnant uterus and has the ability to invade and replicate within cells of the maternal–fetal unit, including trophoblasts and decidual cells. Placentitis is a common finding in infected pregnant animals. Several proinflammatory factors have been found to be increased in both the placenta of Brucella-infected animals and in trophoblasts or decidual cells infected in vitro. As normal pregnancies require an anti-inflammatory placental environment during most of the gestational period, Brucella-induced placentitis is thought to be associated with the obstetric complications of brucellosis. A few studies suggest that the blockade of proinflammatory factors may prevent abortion in these cases.